Prophylaxis of chemotherapy-induced neutropenia with lipegfilgrastim in patients with lung cancer: final results from the non-interventional study NADIR. (2nd December 2022) - Geßner, Christian; Fietz, Thomas; Losem, Christoph; Lück, Andreas; Schulz, Holger; Niemeier, Beate; Groschek, Matthias; Eschenburg, Henning; Weide, Rudolf; Kretzschmar, Albrecht; Frost, Nikolaj; Hipp, Joachim; et al.
Abstract: Objective: Real-world evidence on the application of the granulocyte colony-stimulating factor lipegfilgrastim for the reduction of chemotherapy-induced neutropenia and febrile neutropenia (FN) is limited. The NADIR study aimed to evaluate effectiveness and safety of lipegfilgrastim as primary or secondary prophylaxis in patients with lung cancer undergoing chemotherapy in routine clinical practice. Methods: The non-interventional study NADIR (German Clinical Trials Register (DRKS) Number DRKS00005711) enrolled 156 patients with small-cell lung cancer (SCLC) and 145 patients with non-small-cell lung cancer (NSCLC), who received lipegfilgrastim during chemotherapy. Primary endpoint was the incidence of severe neutropenia (CTCAE grade 3/4) and FN. The analysis was stratified for age groups (≤65 years vs. >65 years). Results: Approximately half of the patients were aged >65 years (SCLC 54.5%; NSCLC 46.9%). Intention of antineoplastic treatment was mostly palliative (SCLC 89.1%; NSCLC 73.1%). Patients with high FN risk (SCLC 44.9%; NSCLC 28.3%) mostly received lipegfilgrastim for primary prophylaxis (SCLC 81.4%; NSCLC 70.7%). FN was reported in 1.9% SCLC and 1.4% NSCLC patients. At least one severe neutropenia was documented in 30.1% SCLC and 17.9% NSCLC patients. For NSCLC patients aged >65 years, less severe neutropenia was reported as compared to younger patients (14.7% vs. 20.8%). Lipegfilgrastim-related adverse events were reported in 10.3% SCLC and 7.7% NSCLC patients. Conclusion: Lipegfilgrastim in routine clinical practice of patients with lung cancer showed similar effectiveness and safety as compared to the pivotal trial. Interestingly, in older patients severe neutropenia was reported less frequently. While most patients with high FN risk received lipegfilgrastim for primary prophylaxis as recommended, there are still 20–30% of patients at high FN risk without primary prophylaxis who could benefit from better adherence to guidelines.